Iowa RBA, September 15, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for September 15, 1997. Highlights of the update include the continued presence of Eurasian Collared Doves and a sighting of a Black-throated Blue Warbler. Also of note were several reports of Purple Finches and Pine Siskins in the northern part of the state, and Red-breasted Nuthatches being reported state wide. Also included are handwritten notes for the next week's update with sightings of Lark Buntings and a Red-necked Phalarope. Epson - sheet feed/flatbed